Influence of HOTAIR rs920778 and rs12826786 genetic variants on prostate cancer risk and progression-free survival. (March 2018) - Oliveira, Ana Isabel; Xavier-Magalhães, Ana; Moreira-Barbosa, Catarina; Magalhães, Hugo; Henrique, Rui; Jerónimo, Carmen; Costa, Bruno M
Aim: Evaluate the impact of the single nucleotide polymorphisms rs920778 and rs12826786 in the long noncoding RNA HOTAIR in the susceptibility and prognosis of prostate cancer (PCa) patients.Patients & methods: HOTAIR single nucleotide polymorphisms were genotyped by restriction fragment length polymorphism in 151 PCa cases and 180 cancer-free controls. Odds ratio, 95% CIs and prognostic significance were calculated.Results: Our data showed no statistically significant associations between HOTAIR polymorphic variants in rs920778 and rs12826786 and PCa susceptibility. However, the CC genotype in rs12826786 was significantly associated with shorter biochemical recurrence-free survival in pT3-stage PCa patients.Conclusion: Our results indicate that HOTAIR rs12826786 CC genotype may be an independent prognostic biomarker in a particular subset of PCa tumors.